A REVIEW OF ISSUES AND OPPORTUNITIES OF ARCHI-PRENEURSHIP PRACTICE IN NIGERIA - Solomon Oisasoje Ayo-Odifiri (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2023)
This article appraises issues and opportunities of architectural entrepreneurship (archi-preneurship) practice in Nigeria. It recognises the relevance of entrepreneurial orientation in the architectural syllabus as a consequence of the emerging issues facing the career path and derived from students' long-term educational needs to prepare them for a successful job in a competitive global economy. Hence, industrialisation, job creation, and poverty alleviation processes are accentuated by entrepreneurship. To find out these issues and opportunities of archi-preneurship, a systematic review approach was adopted to source current relevant data from Academia, Elsevier, ScienceDirect, Google Scholar, MDPI, and ResearchGate databases for this study, which focused on programmes relating to the architecture profession that can help entrepreneurs grow and make conclusions. The concepts of entrepreneurship, architecture, and technology were explored. Five specialisation areas that would potentially facilitate entrepreneurial prospects in Nigeria were identified, and the challenges they present to architects. These components include architecture consultation; research and application of building information modeling (BIM) technologies; property development and construction, retrofitting and energy efficiency; sustainable building material science; and urban design. Some available skills architecture graduates could engage in include landscaping, interior design, graphics and animation, project management, architecture blogging, forensic architecture, and building pathology among others. The study outlines different aspects that architects should consider to de-emphasise the hunt for non-existent office employment and embrace self-occupation. Also, more entrepreneurial training skills and development programmes should be established, as well as a reassessment of the present syllabi to instill business knowledge at all stages of architecture education.